1988
DOI: 10.5271/sjweh.1922
|View full text |Cite
|
Sign up to set email alerts
|

Impulse noise and hand-arm vibration in relation to sensory neural hearing loss.

Abstract: MSc,' Ilmari Pyykko, MD2 STARCK J, PEKKARINEN J, PYYKKO 1. Impulse noise and hand-arm vibration in relation to sensory neural hearing loss. Scand J Work Environ Health 14 (1988) 265-271. The present study was carried out to determine whether impulse noise and simultaneous exposure to noise and vibration can aggravate sensory neural hearing loss (SNHL) among forest (N = 199) and shipyard (N = 171) workers. The average level of exposure to noise outside the used earmuffs and the average exposure over time were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 30 publications
1
51
0
1
Order By: Relevance
“…In addition, percussion vibratory tools produce impulse noise as well. Impulse noise has been considered to be more likely to cause noise-induced hearing loss than steady state noise is (13). Thus, when the effect of vibration on workers is under consideration, it is important to emphasize the impulsiveness of hand-transmitted vibratory tools (14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, percussion vibratory tools produce impulse noise as well. Impulse noise has been considered to be more likely to cause noise-induced hearing loss than steady state noise is (13). Thus, when the effect of vibration on workers is under consideration, it is important to emphasize the impulsiveness of hand-transmitted vibratory tools (14).…”
Section: Discussionmentioning
confidence: 99%
“…The microphone signal was fed to a signal analyser by a 0.3-mm diameter cable to minimize leakage between skin and cushion ring of the earmuff. In different working sites 10-min samples were recorded for the analyses of Aweighted equivalent sound level and the impulsiveness of the noise (12). For the calculations of paper mill workers exposure to noise a total of 21 measurements at different working sites were taken.…”
Section: Exposure To Noisementioning
confidence: 99%
“…In many occupations the impulses are so brief that they contribute only slightly to the energy content of noise. In our earlier studies we found that shipyard workers had 10 dB greater hearing loss than was predicted by the ISO 1999 model, whereas for forest workers the observed and predicted hearing threshold levels were consistent Starck et al, 1988a). Target-shooting and hunting also augment the risk for hearing loss (Ylikoski et al, 1994).…”
Section: Impulse Noise and Hearingmentioning
confidence: 88%
“…This is due to the high frequency content of the impulses, which are attenuated effectively by earmuffs. Even though earmuffs reduce the impulsiveness of noise, the workers in the metal industry are still exposed to higher impulse noise than the workers in paper mills and in forestry (Starck et al, 1988a). In 10% of the workers examined, the attenuation of HPDs was less than 5 dB (Pekkarinen, 1987).…”
Section: Evaluation Of Hearing Protectorsmentioning
confidence: 98%